INVESTIGATION OF THE COATINGS APPLIED ONTO BRAKE DISCS ON DISC-BRAKE PAD PAIR - (:unkn) unknown (CROATIAN METALLURGICAL SOC, 2009)
While braking, according to the severity of it, thermal, metallurgical, constructive and tribological occurrences emerge on the brake disc-pad interface. In this study, NiCr was sprayed as bonding layer onto the discs, one of which was coated with Al2O3-TiO2 by plasma spray and the other was coated with NiCr-Cr3C2 by High Velocity Oxygen Fuel (HVOF). In addition, the discs were tested with inertia dynamometer according to SAE's J2522 testing procedure. The measurements showed that although the pads of the coated discs were exposed to higher braking temperatures, friction coefficient of the disc coated with NiCr-Cr3C2 was obtained 6% higher compared to the original disc.
Keywords: coating; improving disc performance; Disc Thickness Variation (DTV); Brake Torque Variation (BTV)